2015
DOI: 10.1111/jmwh.12282
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Intracardiac Echogenic Focus on Routine Ultrasound: Implications for Practice

Abstract: Ultrasound is widely used as a screening tool for fetal anomalies. An intracardiac echogenic focus (ICEF) is associated with fetal aneuploidy, particularly trisomy 21, when found with other minor abnormalities known as soft markers. However, when found in isolation, intracardiac echogenic foci are morphologic variations with little or no pathologic significance for the fetus. Ambiguity about the significance of ICEF and other soft markers and the lack of preparation prior to ultrasound can result in unnecessar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 50 publications
0
2
0
Order By: Relevance
“…In this study, 65 fetuses with hyperechogenic bowel had normal karyotyping analysis results, but three fetuses with hyperechogenic bowel had abnormal CNVs. At present, many studies reported that fetuses with echogenic intracardiac focus did not have an increased risk for chromosomal abnormalities [18][19][20], but one pathogenic CNV was detected in 22 fetuses with echogenic intracardiac focus in this study. Therefore, SNP array should be considered when karyotyping analysis is carried out for fetuses with mild tricuspid regurgitation, hyperechogenic bowel, and echogenic intracardiac focus.…”
Section: Discussionmentioning
confidence: 44%
“…In this study, 65 fetuses with hyperechogenic bowel had normal karyotyping analysis results, but three fetuses with hyperechogenic bowel had abnormal CNVs. At present, many studies reported that fetuses with echogenic intracardiac focus did not have an increased risk for chromosomal abnormalities [18][19][20], but one pathogenic CNV was detected in 22 fetuses with echogenic intracardiac focus in this study. Therefore, SNP array should be considered when karyotyping analysis is carried out for fetuses with mild tricuspid regurgitation, hyperechogenic bowel, and echogenic intracardiac focus.…”
Section: Discussionmentioning
confidence: 44%
“…In this study, 65 fetuses with hyperechogenic bowel had normal karyotyping analysis results, but three fetuses with hyperechogenic bowel had abnormal CNVs. At present, many studies reported that fetuses with echogenic intracardiac focus did not have an increased risk for chromosomal abnormalities [17][18][19], but one pathogenic CNV was detected in 22 fetuses with echogenic intracardiac focus in this study. Therefore, SNP array should be considered when karyotyping analysis is carried out for fetuses with mild tricuspid regurgitation, hyperechogenic bowel, and echogenic intracardiac focus.…”
Section: Discussionmentioning
confidence: 47%